A Study on the Application Design of Soil Moisture Diffusion and Crop Roots According to Subsurface Irrigation Method - Kim, Jin Hyun; Kim, Tae Wook; Kim, Seol Ha; Lee, Hwang Gyu; Eum, Duk Ho; Lee, Sang Hun (Journal of Biosystems Engineering, 46(3), 2021)
Purpose Global climate change has increased drought frequency and caused significant damage to agricultural industries worldwide; for example, soybean yield has decreased by 30% on small-scale farms. Therefore, the development of subsurface irrigation methods, which conserve both water and labor, is urgently needed for open-field cropping systems. Although water and nutrient supply through subsurface irrigation shows clear advantages, the specific design of these irrigation systems relies on empirical data rather than systematic research and practical optimization. Because of irregularities and uncertainties in field soil conditions, the theoretical approach for water diffusion in soil frequently could give a wrong range of data to an irrigation system. In this study, the water diffusion by means of a commercial subsurface irrigation system has been experimentally tested in several soil types to get practical application and understand the water diffusion performance. Methods In the present study, to better understand the shape of the subsurface diffusion plume in an open-field soybean crop during irrigation, we supplied 4 L of water through 3 mm vertical tubes using three types of dripper, at transfer rates of 2, 4, and 8 L/h. A map of the wetted soil near the dripper showed that the optimal water supply depends on the growth stage of the soybeans. Results Subsurface irrigation testing was conducted on well-graded sand containing clay (SWC: sand well + sand clay) and poorly graded sand (SP: sand plastic). As both SWC and SP showed that the wetted area rises well upward to the ground surface from the dripping point with 2 L/h supply, it is considered that 2 L/h case is effective for water absorption by the roots of the crops. Besides, the size of the grown root of 30 days showed 450 mm of width and 300 mm of depth, so it was estimated that 150 mm wide and 100 mm deep after 10 days, and 300 mm wide and 200 mm deep after 20 days. Judging from the results of the root growth and water diffusion rate, it is desirable that over 8 L and 5–6 L supply after 10 days and 20 days of the bean sowing, respectively. Also, since the roots after 30 days grow 300 mm deep and reach to water supply drip line, it is appropriate to supply about 4 L. Conclusions We obtained empirical vertical and horizontal diffusion data to characterize soil water transport during subsurface irrigation. In summary, in terms of water supply rate, 2 L/h was the most effective for subsurface irrigation. Additionally, depending on the growth stages of the soybeans, early, 20 days, and 30 days, 8 L, 5–6 L, and 4 L are recommended for the supplied water amount, respectively.